Pengaruh kualitas pelayanan terhadap kepuasan tamu pada hotel berbasis syariah di kota samarinda (studi pada hotel grand sawit kota samarinda) - Intan Solihin; Zainal llmi; Robi Ansyah (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2019)
Intan Solihin, 2019. Influence of Service Quality on Guest Satisfaction in Sharia Based Hotel’s in Samarinda City (Case Study of Grand Sawit Hotel’s in Samarinda City). Under the guidance of Mr. Dr. H. Zainal Ilmi, S.E., M.BA and Mr.Robiansyah, S.E., M.Sc.The phenomenon that occurs at this time is the emergence of similar lodgings in the hotel area of the Grand Sawit Hotel’s Samarinda which is one of the lodgings engaged in services, especially accomodation. With the emergence of similar lodgings, it makes the Grand Sawit Hotel’s Samarinda more applicable to Islamic principles and Islamic values in the hotel.             This study aims to determine the factors that influence guest satisfaction with the quality of service at the Grand Sawit Hotel’s Samarinda. The independent variables in this study are service quality and the dependent variables is the satisfation of hotel guests. This research was conducted to guests who stayed and used the services of the Grand Sawit Hotel’s Samarinda which consisted of 51 respondent.            The type of research used is quantitative research. Methods of collecting data using questionnaires. The technique used for sampling is accidental sampling (sampling technique based on accidental events, namely who is considered appropriate and accidentally met with the researcher). Then the data analysis technique used is in this study id to test the validity, reliability test and multiple linear regression analysis.            The result showed that the effect of service quality on guest satisfaction had an influence on the Grand Sawit Hotel’s Samarinda.